Nanofrustulum fogedii sp. nov., a new araphid diatom (Staurosiraceae, Bacillariophyta) from Spitsbergen (Svalbard archipelago) - Vijver, Bart Van De; Beauger, Aude; Pottiez, Margaux; Wetzel, Carlos E. (Phytotaxa, 2024)
Nanofrustulum fogedii sp. nov. is described based on a historic sample from Spitsbergen collected by Niels Foged. The new species, originally identified by Foged in 1964 as Nanofrustulum (Melosira) cataractarum, can be separated from the latter by its larger valve diameter, longer striae composed of 1–6 transapically elongated areolae and a higher valve mantle. The species was observed in several samples collected from thermal springs in the Arctic Svalbard Archipelago. Based on its major morphological features, such as the quasifract girdle bands, the small valve dimensions and the serrated linking spines, the transfer of another small-celled araphid species, formerly described as Pseudostaurosira bardii Beauger et al. to the genus Nanofrustulum is justified.